Supplementary Surveillance of Poliovirus Circulation in the Russian Federation: Results of a Study on Migrant Children of “Risk Group” - Olga E. Ivanova; Yulia M. Mikhailova; Nadezhda S. Morozova; Alina V. Chirova; Evgeniya A. Cherepanova; Lyudmila N. Golitsyna; Olga Y. Baikova; Elizaveta V. Yakovchuk; Evgenia V. Karpova; Liubov I. Kozlovskaya (Viruses)
The detection of “silent” poliovirus (PV) circulation among clinically healthy populations is an important component of supplementary surveillance for poliomyelitis. Migrants from countries or regions where polio is endemic, affected by outbreaks, or at risk may contribute to the introduction of PVs of epidemic significance: wild poliovirus type 1, vaccine-derived polioviruses (VDPVs), or poliovirus type 2 into polio-free countries. Migrant children, refugees under 5 years of age, are considered a “risk group” in Russia and are subject to testing for PVs. During 2014–2023, guided by the algorithm of virological and molecular investigation of acute flaccid paralysis cases recommended by the WHO, 51,548 migrant children, arriving from 40 countries, were examined. Among 4% of children excreting various cytopathogenic viruses, polio excretors accounted for 20.8%. Among the PVs, PV3 was predominant (41.7%), and PV types 2, 1, and a mixture of PVs accounted for, respectively, 28.2%, 18.8%, and 11.3%. All isolates of PVs 1 and 3 were identified as Sabin-like. The detection of five children excreting epidemically significant PV2 (four VDPV2 and one Sabin-like) required an assessment of the risk of dissemination and additional immunization activities. Among 580 identified isolates of NPEV, the most abundant was the E. betacoxsakie species at 73.8% (CVB1–6, E11, E6, E13, E7). Information on NPEVs expands our knowledge of the spectrum of NPEVs circulating among healthy children worldwide, but its prognostic significance is still unclear. The detection of PVs in children from the “risk group” allows targeted anti-epidemic measures and is a significant advantage of this type of supplementary surveillance for polio.